The Epistemology of Spiritual Education in the West Sumatran Syattariyah Manuscript Tradition: A Living Manuscript as Epistemological Instrument of Sufi Reception - Ahmad Rivauzi; Halomoan Halomoan; Muhammad Yusuf; Wirdati; Mohd Roslan Mohd Nor (Jurnal Lektur Keagamaan, 2026)
This article examines how a Syattariyah teaching manuscript, copied by Shaykh ʼAlī ʼImrān and actively used as a pedagogical text at Pondok Pesantren Nūr al-Yaqīn Pakandangan, West Sumatra, epistemologically receives the teachings of ʼabd al-Raʼūf al-Sinkilī and constructs a framework of spiritual education within the living manuscript tradition of the Syattariyah Order. Previous studies on this order have focused primarily on historical transmission, ritual practice, scholarly networks, and doctrinal debates surrounding waḥdat al-wujūd, while the epistemological role of teaching manuscripts in the production and transmission of spiritual knowledge remains underexplored. This study employs a qualitative, manuscript-based philological-critical analysis guided by Jaussian reception theory, supported by limited contextual interviews with practitioners of the tradition. The analysis reveals three forms of Sufi reception: the preservation of metaphysical substance, the modification of theological terminology, and the localization of spiritual teachings into pedagogical categories. Through these processes, the manuscript constructs an epistemology of spiritual education oriented toward maʼrifatullāh through the integration of metaphysical knowledge, self-knowledge, and transformative spiritual practice. The article demonstrates that the receipt of al-Sinkilīʼs teachings is not merely textual transmission but an epistemological process through which spiritual knowledge is constructed, validated, and transmitted. This contributes to the study of Sufi pedagogy and Nusantara Islamic manuscript traditions by demonstrating that the tarīkat text functions as an epistemological instrument for producing, selecting, validating, and transmitting spiritual knowledge.